Effectivity of Various Swallowing Exercises in Post-Stroke Dysphagia Patients Rehabilitation: Systematic Review - Faza Al-Apdarrovis; Widya Meiliana; Eka Febri Zulissetiana (Sriwijaya Journal of Medicine, 2024)
Post-stroke dysphagia (PSD) affects up to two-thirds of stroke patients, potentially leading to complications such as malnutrition, pneumonia, and increased mortality. This condition results from disrupted neural coordination in the swallowing process, with patients often experiencing severe symptoms. Current treatments combine compensatory strategies and rehabilitative therapies, including swallowing exercises. However, the effectiveness of these exercises remains inconclusive due to small sample sizes and short follow-up periods. This systematic review followed the PRISMA-P 2020 checklist, with literature sourced from PubMed, ScienceDirect, Sage Journals, Cochrane Library, and Proquest using the keywords "Swallowing Exercise" AND "Stroke" AND "Dysphagia.". Eight randomized controlled trials with a total of 278 participants focused on exercises such as head lift exercise (HLE), jaw opening exercise (JOE), oral neuromuscular training, kinesiology taping (KT), Chin Tuck Against Resistance (CTAR), respiratory muscle training (RMT), and community-based rehabilitation. All studies demonstrated improvements in swallowing function, but limitations included small sample sizes, short follow-up periods, and insufficient prior research. This review concludes that swallowing exercises are effective for PSD; however, further research is needed to validate their long-term effectiveness.